Implementing Government Policy in Supply Chains: An International Coproduction Study of Public Procurement. Issue 2 (10th April 2019) - Harland, Christine; Telgen, Jan; Callender, Guy; Grimm, Rick; Patrucco, Andrea
Abstract : Public procurement is the commercial arm of governments, contracting for goods, and services to feed public sector service provision. However, mainstream operations and supply chain management journals have published little on supply chains to governments, public procurement, and the significance of engaging small businesses in government supply chains. Policy feedback theory and thirteen coproduced international case studies of public procurement and small business agency dyadic relationships are used to explore this space. The research highlights the importance of both public procurement and small business as areas of policy and supply chain management research. Policy feedback theory is introduced as a means to understand relationships and is applied to a coproduction study to understand how supply chain management research can both explore and change policy.